2019
DOI: 10.1111/ele.13225
|View full text |Cite
|
Sign up to set email alerts
|

Ionome and elemental transport kinetics shaped by parallel evolution in threespine stickleback

Abstract: Evidence that organisms evolve rapidly enough to alter ecological dynamics necessitates investigation of the reciprocal links between ecology and evolution. Data that link genotype to phenotype to ecology are needed to understand both the process and ecological consequences of rapid evolution. Here, we quantified the suite of elements in individuals (i.e., ionome) and differences in the fluxes of key nutrients across populations of threespine stickleback. We find that allelic variation associated with freshwat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 75 publications
(186 reference statements)
3
21
0
Order By: Relevance
“…This alternative hypothesis is consistent with the observation that phosphorus excretion rates are not inversely related to body phosphorus content in the wild, as is expected under limiting dietary phosphorus conditions (Durston and El‐Sabaawi 2019; Rudman et al. 2019).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This alternative hypothesis is consistent with the observation that phosphorus excretion rates are not inversely related to body phosphorus content in the wild, as is expected under limiting dietary phosphorus conditions (Durston and El‐Sabaawi 2019; Rudman et al. 2019).…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, a recent study of stickleback ionomes found that rare elements, particularly barium, differ consistently between marine and freshwater fish and their native habitats (Rudman et al. 2019). This might be a factor to test in future studies, given the lack of conclusive empirical support for either calcium or phosphorus limitation driving selection for the low‐plated phenotype in freshwater.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a strict definition of eco-evolutionary feedback (Schoener, 2011), two interacting processes would be required: ES traits would have to evolve rapidly in a population and the evolution of these ES traits would need to modify the environment in a way that significantly affects selection on that population. The potential for eco-evolutionary feedbacks mediated by the evolution of ES traits has been much discussed (Jeyasingh et al, 2014;Leal et al, 2017b;Rudman et al, 2019), and some studies have demonstrated that rapid evolution can shape elemental availability (Bassar et al, 2010;Rudman and Schluter, 2016). Yet, whether these differences in elemental availability feed back onto rapid evolution is wholly unknown.…”
Section: Ecological Consequences Of Intraspecific Variation In Es Tramentioning
confidence: 99%
“…These experiments minimize the effects of the environmental factors by comparing genetically distinct individuals within a common "garden" environment, thus allowing for the quantification of genetic variation either within or between populations (Lynch and Walsh, 1998). Synthesis of such studies could illuminate whether genetic variation is present, the relative amount of genetic variation within and across populations, which stoichiometric traits show genetic variation, and whether elemental limitation could influence evolution in nature (Elser, 2006;Leal et al, 2017a;Rudman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%